Perancangan Website UMKM D’KRIUK FRIED CHICKEN Pasar Baru Menggunakan Blogger - Musley Algivari; Fadhel Ahmad Jawry; Torry Malik Ibrahim (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Sales and marketing systems of goods and services via the internet are also in great demand by businesses. By providing a place as a medium for communicating and transacting cyberspace is able to reach the corners of the world making it possible for business communication via the internet.. With an attractive website appearance can also be a special attraction to invite consumers to visit the website. One of the uses of the website is to make it easy to exchange, update information and do business through internet users. A website can be the work of individuals or individuals, or show ownership of an organization, company, and usually the website shows some special topics, or certain interests. The Project Is a Website https://dkriukoutletpadang.blogspot.com/ . the design of the face of an attractive website will encourage visitors to see more deeply the contents of the website and can interact in business and others